Comparative assessment of a flash flood susceptibility map based on morphometric analysis and bivariate statistics in the Upper Citarum Watershed, Indonesia - Wardhani, Fitriany Amalia; Sapan, Elenora Gita Alamanda; Widiatmoko, Nicko; Yuvhendmindo, Muhammad Ravi; Santosa, Budi Heru; Susanti, Wiwiek Dwi; Pravitasari, Andrea Emma; Triwisesa, Endra; Ridwansyah, Iwan (Bulletin of Geography. Physical Geography Series, 2024)
Flash floods are one of the most destructive natural disasters, characterized by rapid occurrence and high casualty rates due to a lack of preparedness. Mapping susceptibility areas to identify flash-flood-prone zones can be an effective tool for mitigation. Despite various flood susceptibility mapping methodologies, research on the most suitable statistical approach for Indonesia’s unique environmental context remains limited. This study aimed to compare the performance of three statistical methods, namely Shannon’s Entropy (SE), Statistical Index (SI) and Frequency Ratio (FR), in assessing flash flood susceptibility. Conducted in the Upper Citarum Watershed, Indonesia, this study used geospatial analysis using elevation, slope, curve number, lithology, soil movement, rainfall and morphometric parameters of the watershed to analyze flash flood susceptibility in the study area, with morphometric characteristics affecting hydrological processes such as surface runoff and soil erosion. The results indicate that the Statistical Index Flash Flood Susceptibility Map (SI FFSM) is the most effective model for representing flash flood susceptibility, achieving the highest AUC values for success rate (0.907) and prediction rate (0.933). According to the SI method, the three most influential parameters driving flash floods in the research area are elevation, landslides or soil movement, and rainfall. The total high and very high flash flood susceptibility area is 102.29 km2 or 46.95% of the study area. The findings of this study will contribute to the development of more-accurate and -practical tools for disaster risk assessment and management, both in Indonesia and other regions with similar environmental conditions.